Adipose tissue distribution in relation to insulin resistance in type 2 diabetes mellitus - Azuma, Koichiro (Am J Physiol Endocrinol Metab, 2007)
Insulin resistance (IR) is typically more severe in obese individuals with type 2 diabetes (T2DM) than in similarly obese non-diabetics but whether there are group differences in body composition and whether such differences contribute to the more severe IR of T2DM is uncertain. DEXA and regional CT imaging were conducted to assess adipose tissue (AT) distribution and fat content in liver and muscle in 67 participants with T2DM (F39/M28, age 60 ± 7 yr, BMI 34 ± 3 kg/m(2)) and in 35 similarly obese, non-DM volunteers (F20/M15, age 55 ± 8 yr, BMI 33 ± 2 kg/m(2)). A biopsy of subcutaneous abdominal AT was done to measure adipocyte size. A glucose clamp was performed at an insulin infusion of 80 mU · min(−1)·m(−2). There was more severe IR in T2DM (6.1 ± 2.3 vs. 9.9 ± 3.3 mg· min(−1) · kg FFM(−1); P < 0.01). Group comparisons of body composition parameters was performed after adjusting for the effect of age, gender, race, height and total fat mass (FM). T2DM was associated with less leg FM (−1.2 ± 0.4 kg, P < 0.01), more trunk FM (+1.1 ± 0.4 kg, P < 0.05), greater hepatic fat (P < 0.05), and more subfascial adipose tissue around skeletal muscle (P < 0.05). There was a significant group × sex interaction for VAT (P < 0.01), with greater VAT in women with T2DM (P < 0.01). Mean adipocyte size (AS) did not significantly differ across groups, and smaller AS was associated with increased leg FM, whereas larger AS was related to more trunk FM (both P < 0.05). Group differences in IR were less after adjusting for group differences in leg FM, trunk FM, and hepatic fat, but these adjustments only partially accounted for the greater severity of IR in T2DM. In summary, T2DM, compared with similarly obese nondiabetic men and women, is associated with less leg FM and greater trunk FM and hepatic fat.